The passengers' perceptions towards the service quality provided by Mara Liner in Klang Valley / Kamil Muhammad - Muhammad, Kamil (Faculty of Business and Management, 2007)
Service quality is inarguably a prerequisite of customer satisfaction. This study seeks to measure the current level of perception among MARA Liner's passengers towards the service quality provided in Klang Valley. Following the suggestion that the European perspective is a more appropriate representation of service quality than the American perspective, the study adopted the European perspective (i.e. Grönroos' model) that suggest service quality consists of three dimensions, technical, functional and image in measuring perceived service quality. Then, this study also examines whether there are relationship between these three dimensions and service quality perception in this industry. A modified SERVQUAL was used to measure functional quality. From a sample size of 50 respondents, the results revealed that all the dimensions registered an average mean score of above 4, thus showing that the passengers perceived the quality of service provided by MARA Liner is good. The results also indicated that all the dimensions, except reliability and responsiveness have relationship with service quality perception. Further, the results revealed that there is no relationship between frequency of using and service quality perception, but the relationship does exist between likelihood to select MARA Liner in future and service quality perception. It is recommended to MARA Liner to focus more on the dimension which shows more obvious relationship as well as maintaining the good service and strengthening the customer relationship marketing.